Assignation of limited resources in pediatrics - Garduño Espinosa Armando; Rosas Vargas Rosaura; Reynés Manzur José (Instituto Nacional de Pediatría, 2014)
Limited resources assignation is fundamental in the development of health services and since they will never be enough, justice is- sues arise. Many distributive justice theories are discussed: liberal, equilable and utilitarian, as well as ethic principles and cost-benefit relation, that is, the consequences. Palliative medicine is suggested as a strategy to reduce the cost of hospitable care and to enhance its designation.